Peran Dongeng dalam Membangun Literasi Anak di Sekolah Dasar - Prasetyo, M. Rizki Prasetyo; Ismiyanti, Yulina; Yustiana, Sari (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Literacy is an essential basic skill for every individual to actively participate in modern society. The development of literacy encompasses not only reading and writing skills, but also comprehension, analysis, and critical thinking abilities. The aim of this research is to explain the role of storytelling in building children's literacy in elementary school. This study uses a case study method, with a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. Data analysis employs techniques of data reduction, data presentation, and drawing conclusions. The results of the study show that the application of storytelling in literacy learning at SD Genuksari 02 Semarang has a positive impact on improving children's literacy. Storytelling not only increases students' interest in reading but also helps them understand texts, enrich vocabulary, and enhance critical thinking and communication skills.